Dark heir - Pacat, C. S. (Pacat, C. S. 2. Dark rise (Series), 2023)
In this riveting sequel to the New York Times bestselling novel Dark Rise, Will and his allies have survived the Dark's first assault, but at a terrible cost. A new threat from the past is rising, and only a handful of heroes remain to fight. Pursued by dark forces, Will and his allies must leave the safety of the Hall and travel to the heart of the ancient world, making new and dangerous alliances, and revealing the shocking secrets of the past. But Will is carrying a dark secret of his own-his true identity. Drawn to the beautiful and deadly James St. Clair, Will is pulled ever deeper into the web of the past, and finds himself tempted by the darkness within. As the ancient world threatens to return, can Will and his friends fight their fate? Or will the truths they learn tear their world apart?